2012
DOI: 10.1111/j.1439-0396.2012.01292.x
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic evaluation of masseter muscle activity in horses fed (i) different types of roughage and (ii) maize after different hay allocations

Abstract: Summary The aims of this study were to monitor electromyographic (EMG) activity of masseter muscle in healthy horses fed (i) different types of roughage and (ii) maize after different hay allocations. Four horses were offered the following three diets ad libitum: hay, haylage or straw/alfalfa chaff (SAC). In a second trial, four horses were fed cracked maize (CM) and hay in three different orders: (i) CM after a 12‐h overnight fast; (ii) CM immediately after restricted hay intake (0.6 kg hay/100 kg BW); or 3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Eating time is regarded as an important equine welfare issue as short eating times may increase the risk of development of oral stereotypies in horses (e.g ., McGreevy, Cripps, French, Green, & Nicol, ; Redbo, Redbo‐Torstensson, Ödberg, Hedendahl, & Holm, ). In a study (Vervuert et al., ) where equine intake time of forage DM was compared between haylage (745 g DM per kg, 384 g crude fibre (CF) per kg DM) and hay (891 g DM and 345 g CF per kg DM) fed ad libitum, both forages were found to give similar DM intake times (52 ± 10.4 and 39 ± 15.3 min per kg DM, respectively, p > 0.05). By monitoring masseter muscle activity in the horses, it was also found that number of chews per kg DM, amplitude of muscle action potential (V) and duration of muscle action potential (sec) was similar between hay and haylage diets, implying that intake and chewing behaviour did not differ between the hay and haylage used in the study (Vervuert et al., ).…”
Section: Impact Of Forage Conservation Methods On Equine Preference Anmentioning
confidence: 98%
“…Eating time is regarded as an important equine welfare issue as short eating times may increase the risk of development of oral stereotypies in horses (e.g ., McGreevy, Cripps, French, Green, & Nicol, ; Redbo, Redbo‐Torstensson, Ödberg, Hedendahl, & Holm, ). In a study (Vervuert et al., ) where equine intake time of forage DM was compared between haylage (745 g DM per kg, 384 g crude fibre (CF) per kg DM) and hay (891 g DM and 345 g CF per kg DM) fed ad libitum, both forages were found to give similar DM intake times (52 ± 10.4 and 39 ± 15.3 min per kg DM, respectively, p > 0.05). By monitoring masseter muscle activity in the horses, it was also found that number of chews per kg DM, amplitude of muscle action potential (V) and duration of muscle action potential (sec) was similar between hay and haylage diets, implying that intake and chewing behaviour did not differ between the hay and haylage used in the study (Vervuert et al., ).…”
Section: Impact Of Forage Conservation Methods On Equine Preference Anmentioning
confidence: 98%
“…It is a major input into musculoskeletal models (Delp et al 2007;Dick et al 2017), and has been used to draw the broad conclusion that muscles tune their operating length to maximize some aspect of performance (Rome and Sosnicki 1991;Herzog et al 1992;Burkholder et al 2001;Tu 2004;Azizi and Roberts 2010;Rubenson et al 2012;Arnold et al 2013;Azizi 2014;Holt and Azizi 2016;Foster and Higham 2017;Nikolaidou et al 2017). However, the variation in activation level with mechanical demand (Lieber and Brown 1992;Gorassini et al 2000;Hodson-Tole and Wakeling 2007;Morris and Askew 2010;Vervuert et al 2013;Seven et al 2014), and the activation-dependent shift in optimum length (Rack and Westbury 1969;Close 1972;Stephenson and Wendt 1984;Balnave and Allen 1996;Holt and Azizi 2014), suggest these predictions and interpretations may be subject to systematic errors.…”
Section: Implications For Understanding In Vivo Muscle Performancementioning
confidence: 99%
“…Activation level has been observed to vary as a function of speed during locomotion [31][32][33], substrate type during feeding [34] and gas composition during breathing [35]. Hence, if muscles always perform optimally, operating lengths and velocities should change with activation level in order to track the changes that occur in optima [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%